2015
DOI: 10.3390/molecules201119691
|View full text |Cite
|
Sign up to set email alerts
|

Auraptene Acts as an Anti-Inflammatory Agent in the Mouse Brain

Abstract: Abstract:The anti-inflammatory activity of auraptene (AUR), a citrus coumarin, in peripheral tissues is well-known, and we previously demonstrated that AUR exerts anti-inflammatory effects in the ischemic brain; the treatment of mice with AUR for eight days immediately after ischemic surgery suppressed demise and neuronal cell death in the hippocampus, possibly through its anti-inflammatory effects in the brain. We suggested that these effects were at least partly mediated by the suppression of inflammatory me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…It has been reported that three flavonoids (naringin, neoponcirin and poncirin) and three coumarins (umbelliferone, imperatorin and auraptene) isolated from the 70% ethanolic extract of Ponciri fructus have various pharmacological actions including antioxidant [27], anxiolytic-like [28], anticancer [29], and anti-inflammatory effects [30][31][32]. Therefore, we propose that PFE can have antiproliferative and antioxidant effects based on the various pharmacological activities of the chemical-chemical interactions on the development and progression of lesions in a TP-induced model of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that three flavonoids (naringin, neoponcirin and poncirin) and three coumarins (umbelliferone, imperatorin and auraptene) isolated from the 70% ethanolic extract of Ponciri fructus have various pharmacological actions including antioxidant [27], anxiolytic-like [28], anticancer [29], and anti-inflammatory effects [30][31][32]. Therefore, we propose that PFE can have antiproliferative and antioxidant effects based on the various pharmacological activities of the chemical-chemical interactions on the development and progression of lesions in a TP-induced model of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation, in particular microglial activation, has recently been attracting a great deal of attention as the key player in PD because activated microglia have been observed to enclose the lost dopaminergic neurons in the brains of PD patients and PD animal models [12,13]. When taken together with our findings that AUR suppressed the activation of microglia in ischemic brains [9,10] and inflammatory brains [11], we were prompted to investigate the effects of AUR on the brains of LPS-induced PD model mice. In the present study, we observed that AUR suppressed microglial activation and subsequent dopaminergic neuronal cell death in the SN of the brains of LPS-induced PD model mice, as expected.…”
Section: Discussionmentioning
confidence: 71%
“…Nevertheless, Okuyama et al recently reported the ability of AUR to penetrate the brain [10]. The permeability of 7-IP and GOFA through the blood-brain-barrier (BBB) will be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations